LOS PROGRAMAS DE TELEVISIÓN INFANTILES Y SU INFLUENCIA EN EL COMPORTAMIENTO DE LOS MENORES DE EDAD EN EL SECTOR “DIVINO NIÑO” DEL CANTÓN QUEVEDO – 2019 - MORALES ALVIA, ELIANA KATHERINE (2020)
Television today is considered one of the most attractive means in the family environment; since most of its audience are minors, since children are the ones who have the highest rating in watching children's television programs. Its great influence through this means of television communication which leads us to have more importance and pay more attention in what certain children's television programs share to our children in the home and thus see their effects and influence. We must analyze what is exposed on television, sit with them, and tell them if the television content they see is right or wrong, and thus does not alter their behavior and behavior; since it is difficult for children to distinguish between fiction and reality.